# Difference between revisions of "Integration by parts for delta integrals with sigma in integrand"

From timescalewiki

(Created page with "==Theorem== The following formula holds: $$\int_a^b f(\sigma(t))g^{\Delta}(t) \Delta t = (fg)(b) - (fg)(a) - \int_a^b f^{\Delta}(t)g(t) \Delta t,$$ where $\int$ denotes the ...") |
|||

(One intermediate revision by the same user not shown) | |||

Line 1: | Line 1: | ||

+ | __NOTOC__ | ||

==Theorem== | ==Theorem== | ||

The following formula holds: | The following formula holds: | ||

Line 5: | Line 6: | ||

==Proof== | ==Proof== | ||

+ | |||

+ | ==See also== | ||

+ | [[Integration by parts for delta integrals with no sigma in integrand]]<br /> | ||

==References== | ==References== |

## Latest revision as of 14:47, 13 March 2018

## Theorem

The following formula holds: $$\int_a^b f(\sigma(t))g^{\Delta}(t) \Delta t = (fg)(b) - (fg)(a) - \int_a^b f^{\Delta}(t)g(t) \Delta t,$$ where $\int$ denotes the delta integral.

## Proof

## See also

Integration by parts for delta integrals with no sigma in integrand